2018
DOI: 10.1142/s0219876218500548
|View full text |Cite
|
Sign up to set email alerts
|

Some Novel Numerical Applications of Cosserat Continua

Abstract: Cosserat continua demonstrated to have peculiar mechanical properties, with respect to classic Cauchy continua, because they are able to more accurately describe heterogeneous materials, as particle composites and masonry-like material, taking into account size effects. Many studies have been devoted to their numerical implementation. In this paper, some reference benchmarks, referred to an isotropic heterogeneous sample, are shown by comparing the solutions provided by strong and weak formulations. The strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…The above-mentioned results are in accordance with the existing literature [32,48]. In the following subsections, the comments about each model with different scale ratios will be detailed with focusing on the conducted non-local theory.…”
Section: Numerical Simulationssupporting
confidence: 85%
See 3 more Smart Citations
“…The above-mentioned results are in accordance with the existing literature [32,48]. In the following subsections, the comments about each model with different scale ratios will be detailed with focusing on the conducted non-local theory.…”
Section: Numerical Simulationssupporting
confidence: 85%
“…N is employed for interpolation of nodal in-plane displacements and consists of quadratic interpolation functions, while  N is employed for nodal out-of-plane micro-rotations, and includes linear type shape functions. As it was mentioned in Fantuzzi et al, [32], and Fantuzzi et al, [33], and clearly showed in the Fig. 1(a), all the nodes of the nine-node Lagrange element possess displacement-type DOFs, whereas micro-rotation DOFs are attached only to the four corner nodes:…”
Section: Finite Element Formulationmentioning
confidence: 65%
See 2 more Smart Citations
“…The same coarse-graining procedure is used which can be shown to be actually dependent both on the brick size, shape and texture of the original (fine) lattice model. The simulations have been carried out for a panel under localized loads, using a standard finite element approach based on a micropolar finite element implementation, with quadratic and linear interpolation functions for the displacement and rotation fields, developed in Fantuzzi et al (2018) following the approach in Providas and Kattis (2002) and implemented within Comsol Multiphysics© framework (Comsol, 2017). The results are presented in terms of contour plots of displacement, stress and relative rotation, the significant strain measure related to the non-symmetrical part of the strain.…”
Section: Introductionmentioning
confidence: 99%